Knowledge, Awareness and Attitude about Breast Lump among Females Attending Mahatma Gandhi Ayurved Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Breast lump is considered as carcinogenic unless it is tested and diagnosed as other than this.Today in India, it is one of the main causes of cancer deaths among women. Only early detection and earlymedical intervention could decrease its mortality rate. Knowledge and awareness of palpation of breastlumps and attitude to get diagnosed at earliest is extremely crucial. Aims & Objectives: Aim is to assessknowledge, awareness and attitude about breast lumps in women attending Hospital OPD. Objectives areto assess the existing knowledge and awareness and to study the attitude about breast lump examinationfor prevention & early diagnostic measures. Methodology: The proposed cross sectional observationalstudy will be carried out in in Mahatma Gandhi Ayurved Hospital, Salod (H),Wardha. The women visitingOPD will be randomly selected and with their consent will be interviewed personally by a structured andvalidated questioner. Result: Result will be interpreted on the basis of statistical analysed data. Conclusion:Conclusion will be drawn from the observations and analysis.
Keywords: Breast lump, Breast self examination, Clinical Breast examination